Assessing Community Involvement and the Achievement of Sustainable Development Goals in APPGM-SDG Sarawak North Solution Projects - Lepun, Philip; Morris Kapong, Joyce; Alan, Ribka; Buang, Fakhzan; Clarence Cluny, Peter (Journal of Technical Education and Training, 2025)
Sarawak North conducted impact assessments on 18 solution projects encompassing five parliamentary constituencies. The projects, implemented by the Solution Providers, involved eight Sustainable Development Goals (SDGs) projects enhance development in specific areas. Therefore, the objectives of this study were: 1) to determine the involvement of the community in the solution projects in Sarawak North, 2) to analyse the impact of solution projects on beneficiaries and stakeholders, and 3) to analyse the impact on SDGs in relations to targets and indicators in Sarawak North. This study utilised a qualitative approach to data collection and analysis comprised of (i) document analysis, (ii) focus group discussion (FGD), and (iii) site visits. This evaluation revealed that 500 participants, from teenagers to the elderly were involved in the solution projects. In terms of gender involvement, women were seen to be more active, indicated by a total of 80.4% participation in projects in North Sarawak and the score value of five contributed by Y22-SP090, Y22-SP023, Y22-SP062 and Y22-SP187. The average score of projects evaluated in this assignment is 3.5, categorised as high-level. This shows that the solution project significantly impacted the lives of the people involved, especially in improving the quality of education, with a mean score of 4.2 and a knowledge dimension of 3.8. In conclusion, development projects awarded to local communities that need economic improvement must be meticulously planned to help in the community’s way of life practices in the future.